Dreams of Glory : the Sources of Apocalyptic Terror. - Fenn, Richard K. (Ashgate Pub., 2007)
Islam, Judaism, and Christianity are engaged not in a 'clash of civilizations' but in a sectarian conflict among branches of a single civilization traditionally steeped in apocalyptic imagery and beliefs. Apocalypticism is a religious luxury that modern civilizations can no longer afford. Many would agree that the propagandists of the Christian Right have raised apocalyptic tensions to a dangerous level since 9/11, but in this book Fenn takes on the main line church leaders for their role in promoting an apocalyptic view of history.